Deep Brain Stimulation for Tourette Syndrome: Potential Role in the Pediatric Population. (February 2020) - Deeb, Wissam; Malaty, Irene
Tourette syndrome (TS) is a complex neuropsychiatric disorder. Despite an expected natural history of improvement with age, many individuals continue to have severe tics and remain refractory to the current best pharmacologic and nonpharmacologic treatments. Deep brain stimulation (DBS) has emerged as a potential treatment option. This article reviews the published reports on the use of deep brain stimulation in Tourette syndrome revealing that 2 anatomical targets have been most commonly used: the centromedian thalamus and the globus pallidus internus. The evidence supports a significant clinical improvement of tics with deep brain stimulation, though the data are limited by the small number of patients and variable methodology employed. To bridge these limitations, the international Tourette syndrome deep brain stimulation database and registry have been created, fostering collaboration among multiple centers from 10 countries. By standardizing data collection, the database and registry are providing valuable insights into deep brain stimulation for Tourette syndrome. In conclusion, deep brain stimulation offers significant promise for the management of tics.